Transcriptomic and physiological analyses reveal different grape varieties response to high temperature stress - Dou, Feifei; Phillip, Fesobi Olumide; Liu, Gang; Zhu, Jingjing; Zhang, Lipeng; Wang, Yongkang; Liu, Huaifeng (Frontiers in Plant Science, 2024)
Abstract High temperatures have an impact on grape yield and quality. Grapes can develop thermotolerance under extreme temperature stress. However, little is known about the alterations in transcription that occur as a result of high temperature stress. The heat resistance indices and transcriptome data of five grape cultivars, ‘Xinyu’ (XY), ‘Miguang’ (MG), ‘Summer Black’ (XH), ‘Beihong’ (BH), and ‘Flame seedless’ (FL), were compared in this study to evaluate the similarities and differences between the regulatory genes and to understand the mechanisms of heat stress resistance differences. High temperatures caused varying degrees of damage in five grape cultivars, with substantial changes observed in gene expression patterns and enriched pathway responses between natural environment conditions (35 ± 2 ℃) and extreme high temperature stress (40 ± 2 ℃). Genes belonging to the HSPs, HSFs, WRKYs, MYBs, and NACs transcription factor families, and those involved in auxin (IAA) signaling, abscisic acid (ABA) signaling, starch and sucrose pathways, and protein processing in the endoplasmic reticulum pathway, were found to be differentially regulated and may play important roles in response of grape plants to high temperature stress. In conclusion, the comparison of transcriptional changes among five grape cultivars reveals a significant variability in the activation of key pathways that influence the grape's response to high temperatures. This enhances our understanding of the molecular mechanisms underlying grape response to high temperature stress.